Breast Cancer Mortality Trends and Predictions to 2030 and Its Attributable Risk Factors in East and South Asian Countries - Mubarik, Sumaira; Sharma, Rajesh; Hussain, Syeda Rija; Iqbal, Mujahid; Nawsherwan,; Liu, Xiaoxue; Yu, Chuanhua (Frontiers in Nutrition, 2022)
Background: Amidst rising breast cancer burden in Asia, we sought to predict the future mortality risk due to breast cancer, and to identify the risk-attributable deaths for breast cancer among East and South Asian countries. Methods: We used country-level data to predict the trends in breast cancer mortality trends by employing data from 1990 to 2019. We used the stochastic mortality modeling and prediction techniques to forecast the age-specific and risk-attributable breast cancer mortality trends at the regional and national level of East and South Asia. Results: Breast cancer mortality is predicted to decline slightly in East Asia and is expected to rise in South Asia, during the next decade (2020-2030). Significantly higher percent change in BC mortality between 2020 and 2030 for age group 80-84 years was observed in South Korea 18.4 (95%Prediction Interval: 5.7-32.7) and North Korea 4.1(1.3-6.9) among East Asian regions. In South Asia, the highest percent change is predicted in Pakistan 23.3(12.9-34.6), followed by Afghanistan 11.5(6.6-16.6) in the next decade. In female population of age 50 to 80 years, the highest death rates are attributed to high-body-mass index, high-fasting plasma glucose and diet high in red meat, among most of the countries under study. Furthermore, reductions in percent change in mortality rates occurred in several countries with increases in SDI, notably across locations belonging to high-SDI quintiles. Conclusions: Breast cancer mortality risk varies tremendously across east and south Asian countries with higher mortality risk in low/middle SDI countries. Early detection using screening, awareness among females and health workers, cost-effective and timely treatment of breast cancer patients holds the key in stemming the tide of breast cancer in next decade.